2012
DOI: 10.1016/j.ydbio.2011.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Multiple origins, migratory paths and molecular profiles of cells populating the avian interpeduncular nucleus

Abstract: The interpeduncular nucleus (IP) is a key limbic structure, highly conserved evolutionarily among vertebrates. The IP receives indirect input from limbic areas of the telencephalon, relayed by the habenula via the fasciculus retroflexus. The function of the habenulo-IP complex is poorly understood, although there is evidence that in rodents it modulates behaviors such as learning and memory, avoidance, reward and affective states. The IP has been an important subject of interest for neuroscientists, and there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 74 publications
6
67
0
1
Order By: Relevance
“…Nkx6-1 + cells have been previously described in the rostral part of the avian IPN (Lorente-Canovas et al, 2012). Consistent with this, numerous glutamatergic Nkx6-1 + Vsx2…”
Section: Molecular Markers and Development Of Rmtg Gabaergic Neuronssupporting
confidence: 84%
See 1 more Smart Citation
“…Nkx6-1 + cells have been previously described in the rostral part of the avian IPN (Lorente-Canovas et al, 2012). Consistent with this, numerous glutamatergic Nkx6-1 + Vsx2…”
Section: Molecular Markers and Development Of Rmtg Gabaergic Neuronssupporting
confidence: 84%
“…S1E-Eb). This is also supported by gene expression and fate-mapping data from avian embryos (Lorente-Canovas et al, 2012). We found that some Pax7 + precursors co-expressed Zfpm2 but no other Gata-or Tal-related factors ( Fig.…”
Section: Foxp1supporting
confidence: 82%
“…Given that the PMC cells lie in the gbx expression region (54), and some of them also are positive for pax4/6 (Fig. 2F), their molecular identity resembles that of the vertebrate interpeduncular nucleus located in the hindbrain and involved in locomotor control (55). Taken together, these findings indicate that in amphioxus the frontal eye projects to the neurosecretory/tegmental neuropil and to the locomotor center, like the eye and the pineal gland in vertebrates.…”
Section: Discussionmentioning
confidence: 71%
“…Subsequently during development, many cells appeared to migrate tangentially into the adjacent basal plate ( Figure 7O ) to reach the interpeduncular nucleus ( Figure 7P ). This situation is conserved through amniotes ( Figures 8D,H ), where Pax7 positive cells of the alar plate migrate into the basal plate during development to finally be a subpopulation of the interpeduncular complex (Lorente-Cánovas et al, 2012). …”
Section: Resultsmentioning
confidence: 96%
“…In developing amphibians, conspicuous Pax7 cell groups are widely distributed in the large r1, starting at early embryonic stages (Bandín et al, 2013; Joven et al, 2013b), like in birds and mammals (Aroca and Puelles, 2005). Comparatively, it is interesting to note that several neuronal populations were reported (in chick and mouse embryos) to be generated in the r1 alar plate, which migrate ventralwards into the medial basal plate, forming a sizeable part of the interpeduncular nucleus complex, apart other medial tegmental nuclei, along their migration pathway (Lorente-Cánovas et al, 2012; Moreno-Bravo et al, 2014). This migratory stream is exclusively present in r1 mantle (absent at isthmus proper and rest of rhombomeres) and was characterized as expressing Pax7, a transcription factor whose signal in the whole hindbrain is otherwise restricted to the alar ventricular zone (Ju et al, 2004).…”
Section: Discussionmentioning
confidence: 99%